2018
DOI: 10.1002/anie.201803076
|View full text |Cite
|
Sign up to set email alerts
|

Wrapping Nanocellulose Nets around Graphene Oxide Sheets

Abstract: Constructing advanced functional nanomaterials with pre-designed organized morphologies from low-dimension synthetic and biological components is challenging. Herein, we report an efficient and universal amphiphilicity-driven assembly strategy to construct "hairy" flexible hybrid nanosheets with a 1D cellulose nanofibers (CNFs) net conformally wrapped around 2D graphene oxide (GO) monolayers. This interface-driven bio-synthetic assembly is facilitated by tailoring the surface chemistry of flexible GO sheets, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
73
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(77 citation statements)
references
References 71 publications
4
73
0
Order By: Relevance
“…16 During the past few years, researches have revealed many encouraging facts and findings regarding the immense potential of graphenebased membranes for separating not only gases but also ions [17][18][19][20][21][22][23][24] and liquids (aqueous/non-aqueous). [25][26][27][28] In this concise review, we provide a brief synopsis of the recent advances in graphenebased gas-separable membranes and the challenges associated for their use as next-generation industrial membranes.…”
Section: Mingdong Dongmentioning
confidence: 99%
“…16 During the past few years, researches have revealed many encouraging facts and findings regarding the immense potential of graphenebased membranes for separating not only gases but also ions [17][18][19][20][21][22][23][24] and liquids (aqueous/non-aqueous). [25][26][27][28] In this concise review, we provide a brief synopsis of the recent advances in graphenebased gas-separable membranes and the challenges associated for their use as next-generation industrial membranes.…”
Section: Mingdong Dongmentioning
confidence: 99%
“…A simple way to improve the dimensional and mechanical stability of lightweight and hydrophilic GO based materials, especially in wet environments, consists on GO reduction, thus removing oxygen containing functional groups and, consequently, decreasing its original hydrophilicity (Wen, Wu, Zhang, Li, & Shi, 2017) (Xiong et al, 2018). Besides, the tailoring of GO surface chemistry by reduction could help to increase its reactivity for amphiphilicity-driven assembly strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the tailoring of GO surface chemistry by reduction could help to increase its reactivity for amphiphilicity-driven assembly strategy. Recently, Xiong et al (Xiong et al, 2018) reported an efficient approach for constructing hybrid materials based on a net of 1D cellulose nanofibers wrapped in GO nanosheets. Their findings showed that the interface-driven assembly between the two components is mainly governed by the level of reduction of GO nanosheets, where highly reduced GO are tightly surrounded by a dense conformal nanocellulose network (Xiong et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Yu et al fabricated various cation‐modified GO membranes and concluded that Al 3+ ‐crosslinked GO (Al‐GO) membrane is more stable than GO membranes crosslinked with mono and di‐valent cations . Furthermore, Xiong et al fabricated GO nanosheets encapsulated with cellulose nanofibers by manipulating the functional groups' interactions to form strong amphiphilic nanosheets that possess high water flux and efficiently reject dyes and gold nanoparticles . Another example is covalent crosslinking with poly(ethylene glycol) (PEG) by Coleman et al, who reported that PEG acts as a steric blocker to widen the interlayer distance between adjacent GO nanosheets .…”
Section: Introductionmentioning
confidence: 99%